Impact of propofol versus sevoflurane on the incidence of postoperative delirium in elderly patients after spine surgery: study protocol of a randomized controlled trial - Ji-hua Wang; Meng Lv; Hai-xia Zhang; Yang Gao; Ting-ting Chen; Tian-tian Wan; Yue-lan Wang (Trials, 2022)
Abstract Background Postoperative delirium in elderly patients is a common and costly complication after surgery. Propofol and sevoflurane are commonly used anesthetics during general anesthesia, and the sedative and anti-inflammatory mechanisms of the two medications are different. The aim of this trial is to compare the impact of propofol with sevoflurane on the incidence of postoperative delirium in elderly patients after spine surgery. Methods A single-center randomized controlled trial will be performed at First Affiliated Hospital of Shandong First Medical University, China. A total of 298 participants will be enrolled in the study and randomized to propofol infusion or sevoflurane inhalation groups. The primary outcome is the incidence of delirium within 7 days after surgery. Secondary outcomes include the day of postoperative delirium onset, duration (time from first to last delirium-positive day), and total delirium-positive days among patients who developed delirium; tracheal intubation time in PACU; the length of stay in PACU; the rate of postoperative shivering; the rate of postoperative nausea and vomiting; the rate of emergence agitation; pain severity; QoR40 at the first day after surgery; the length of stay in hospital after surgery; and the incidence of non-delirium complications within 30 days after surgery. Discussion The primary objective of this study is to compare the impact of propofol and sevoflurane on the incidence of postoperative delirium for elderly patients undergoing spine surgery. The results may help inform strategies to the optimal selection of maintenance drugs for general anesthesia in elderly patients undergoing spine surgery. Trial registration ClinicalTrials.gov NCT05158998 . Registered on 14 December 2021